EDUKASI SELF CARE BERBASIS INDEK MASSA TUBUH TERHADAP PENURUNAN NYERI DISMENORE PADA REMAJA PUTRI - Ana Maria; Leni Wijaya (Jurnal Kesehatan dan Pembangunan, 2026)
Dysmenorrhea is a condition of pain or cramps that occurs during menstruation. According to the World Health Organization (WHO) in 2023, approximately 1,764,425 women (90%) worldwide experience dysmenorrhea, of which 10–16% are classified as severe cases. This study aimed to determine the effect of BMI-based self-care education on dysmenorrhea pain among female adolescents at Izatul Qur’an Lubai Ulu Islamic Boarding School in 2025. This study employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The sample consisted of 23 respondents. Data were collected using an observation sheet in the form of the Multidimensional Scoring System (VMS), completed by respondents before and after the intervention. Based on the non-parametric statistical test (Wilcoxon), the results showed a Z value of ?2.605 with a p-value of 0.009 (p < 0.05), indicating a significant difference between self-care education before and after the intervention, with a tendency toward improved self-care following the education. There is a significant effect of self-care education on reducing dysmenorrhea pain levels and improving body mass index among adolescents. The results of this study are expected to serve as a reference and be further developed by future researchers, particularly by conducting studies on activity-related factors during dysmenorrhea.